Next-Gen Data Security Using Hybrid Cryptography and Email-Based Two-Factor Authentication - Vamsi, Nadakuditi Vijay; Chintala, Radhika Rani (Journal of Neonatal Surgery, 2025)
Now-a-days it must be mandatory for the organization to properly secure data using cryptographic techniques-the advancing digital communication and cloud storage. Despite the effectiveness of hybrid encryption mechanisms used in the traditional models, they are not easily implemented in the environment where there is high throughput because of the bottleneck in performance and vulnerability. An original algorithm in hybrid cryptography, ARB3, is brought forward in this paper. This next-generation algorithm combines the merits of Advanced Encryption Standard (AES), Rivest-Shamir-Adleman (RSA), and the BLAKE3 hashing algorithm. The three components brought together form a fast, secure, and efficient data protection mechanism: high speed symmetric encryption from AES, secure key establishing capabilities from RSA, and fast and secure hashing for data integrity verification from BLAKE3. This model also adds an electronic email 2FA to give an extra layer to access control and user verification: time-sensitive one-time passwords issued to their registered email account. Through rigorous test cases, ARB3 has been found to perform better as regards both encryption and decryption speed and throughput improvements over common cyber threats against traditional models. Hence, this hybrid model is scalable and robustly geared up to provide a state-of-the-art solution for contemporary applications where the demand for high-performance adaptable crypto systems is becoming more urgent.